The Role And Importance Of Small Business In The Economy (Texas Journal of Multidisciplinary Studies, 2025)
Small businesses play a fundamental role in shaping the economic structure of both developing and developed countries. Their importance lies not only in their contribution to gross domestic product (GDP) but also in their ability to generate employment, foster innovation, and stimulate local and regional development. Unlike large corporations, small businesses are often more flexible, adaptable to market changes, and capable of serving niche markets, which makes them crucial in times of economic uncertainty. This paper explores the multifaceted contributions of small businesses to national economies. It highlights how small enterprises serve as a backbone of economic growth by creating jobs, improving income distribution, and encouraging entrepreneurship. In many countries, particularly in emerging markets, small businesses account for the majority of the workforce and play a key role in reducing poverty and inequality